KOMPARASI ANTARA CERITA CINDERELLA DALAM FORMAT DONGENG DAN FILM - Tamara, Dinda (Institut Seni Budaya Indonesia Bandung, 2017)
Story is the most important element in creating a movie. A good movie has a strong story and able to connect emotionally with the audience. A story in a movie, many designed not only specifically for the production of a film, but can also be produced in other formats, such as games or television series. In fact, many of the story films that adapt from other media, namely literary. By using the method of narrative analysis and the theory of ecranization, in this study the authors found many changes when a literary work of writing was lifted into the production of film/ big screen. The case example in this paper is the story of Cinderella who was lifted into the film. Cinderella tells the story of a hope, that there will be a reward for those who are patient. Cinderella is one of the most popular classical tales of all time that has been widely adapted into various media, one of which is the widescreen film produced by Walt Disney in 2015. This paper analyzes the plot comparison between Charles Perrault's Cinderella tale with a film produced by Walt Disney in 2015 with the same title. Through this paper, the authors hope to give an idea of the differences and reasons for plot changes when a story moves formats from one media to another.